Construction of Porous Hierarchical Manganese Dioxide on Exfoliated Titanium Dioxide Nanosheets as a Novel Electrode for Supercapacitors. (1st October 2015) - Zhu, Huimin; Liu, Qi; Liu, Jingyuan; Li, Rumin; Zhang, Hongsen; Hu, Songxia; Li, Zhanshuang
Graphical abstract: Highlights: MnO2 nanoforests were decorated on 2D TiO2 nanosheets by a facile and novel method. The tremella-on-sheet MnO2 /TiO2 composite shows 3D hierarchical porous structure. Conductive TiO2 nanosheets substrate facilitates the contact of electrolyte with deposited MnO2 . The MnO2 /TiO2 composite exhibits excellent capacitive performance. Abstract: A facile composite of tremella-on-sheet manganese dioxide (MnO2 )/titanium dioxide (TiO2 ) has been fabricated successfully as the electrode material for supercapacitors. The results of scanning electron microscopy and transmission electron microscopy reveal that hierarchical tremella-like MnO2 grows onto the exfoliated two-dimensional (2D) TiO2 nanosheets. The uniquely structured composite covers a large specific surface area with typical mesoporous characteristics for achieving high pseudocapacitance performance. The composite exhibits higher specific capacitance (286.69 F g −1 at a current of 1 A g −1 ) and has 81.1% retained specific capacitance after 1000 cycles in three-electrode system. The high performance of the electrode is attributed to a unique structure, 3D hierarchical morphology, particular conductive substrate, and low contact resistance.